Perancangan Komunikasi Visual Revolt Industry Menggunakan Teknik Fotografi Sebagai Upaya Meningkatkan Brand Awareness - Suwandi, Fikri; Riyanto, Darwin Yuwono; Yurisma, Dhika Yuan (Jurnal Art Nouveau, 2017)
Visual communication is a way of communicating through a visual picture or later will be the identity of the product. Visual communication into a means of conveying information and instructions fatherly, aims to show the relationship between a thing with other things such as pointers, direction, position, and scale. Taking one brand from Surabaya namely Revolt Industry to do the design of visual communication Revolt Industry uses photography as an effort to increase brand awareness. Problems in this final project is how to design a visual communication in Revolt Industry products such as efforts to increase brand awareness in order to increase sales had declined in the last 6 months. The research method uses qualitative methods with data collection technique using observation, interviews, literature, existing studies, and study competitors. The concept used in the design is "interesting". Results from the design of the visual communication industry Revolt is an attempt to communicate the products Revolt Industry so that more people know Revolt Industry as well as educate the public about the quality of handmade goods. Designed visual communication is a form of image products Revolt community Industry to easily recognize and remember the product.Keywords: Visual Communications, Photography, Interesting, Brand Awareness.